Es Krim Ekstrak Daun Ubi Jalar Ungu sebagai Alternatif Layanan Kebidanan terhadap Kecukupan Asi pada Ibu Post Partum - Ratnasari, Novi Nur; Mardiyono, Mardiyono; Indrati DS, Dina (Journal of Telenursing (JOTING), 2024)
This research aims to show that purple sweet potato leaves can be extracted and made into ice cream to increase the adequacy of breast milk given to postpartum mothers. The research method used was True Experiment and Pretest-Posttest Design with Control. The study results showed a significant difference in the two intervention and control groups in the breast milk adequacy variable, namely baby weight p-value 0.000 and baby BAK (p=0.000). In conclusion, the ice cream intervention with purple sweet potato leaf extract for 14 days was effective in increasing breast milk adequacy compared to the control group. Purple sweet potato leaf extract had a lactogogum effect on postpartum mothers in stimulating breast milk production. Keywords: Breast Milk, Purple Sweet Potato Leaf Extract, Ice Cream, Postpartum